EFEKTIFITAS KOMPOS CAMPURAN AMPAS TEH, KOTORAN SAPI DAN KOTORAN KAMBING TERHADAP SERAPAN N PADA TANAMAN BAWANG DAUN PADA INCEPTISOL - Santika Patna Dyasmara; S Syekhfani; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
Inceptisols are young soils that have undergone further development are characterized by low nitrogen content, low organic matter contend, and low pH. Fertilizer application is therefore needed to improve fertility of the soils. Tea waste that is easily found at home or factories can be used as organic fertilizer to supply nutrient elements in the soil. The purpose of this study was to elucidate the influence of application of combined compost (mixture of tea waste, cow dung and goat dung) on N uptake by leek plant (Allium fistulosum L.). Eight treatments (control, 5%, 25%, 50%, 75%, 100%, 125%, and 150% compost) were arranged in a completely randomized design with three replicates. The results showed that application of combined compost of tea waste, cow dung and goat dung significantly affected soil pH, soil organic carbon, soil total N, N uptake by plant, plant growth and plant yield. The highest N uptake by plant was observed for treatment 100% compost application (9.1 t ha-1) that yielding 114.62 mg plant-1, while the lowest N uptake was found on the control treatment that yielding only 54.98 mg plant-1.